Peningkatan Kreativitas Siswa dalam Proses Belajar dengan Model Problem Based Learning pada Materi Suara Hati Fase E Kelas X SMA Negeri 2 Mejayan - Ellen Dwi Ratnasari; Anselmus Yata Mones; Maria Margaretha Dwilinda (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This article was written based on the results of observations while teachers were taking PPL while pursuing professional teacher education. From the research, it was found that students' learning creativity was lacking due to the use of monotonous learning models and not using appropriate approaches for each subject matter. For this reason, the author tries to apply the Problem Based Learning learning model. Problem-based learning or better known as PBL is a learning model that is centered on students by providing problems from the real world at the start of learning. With this learning model, it is hoped that it can increase student learning creativity. This research aims to examine the effectiveness of problem-based learning (PBL) in increasing students' creativity in studying the material